2011
DOI: 10.1017/s0022215111000053
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic gentamicin in Ménière's disease: our experience

Abstract: This intratympanic gentamicin injection protocol enabled effective vertigo control in most patients, and represents a good alternative to more aggressive techniques for the treatment of Ménière's disease which does not respond to medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…[14] In a study conducted by Delgardo LP et al in 2011 on 71 patients showed an improvement of vertigo in 84.37% of patients and hearing loss in 18.3% patients. [15] De Beer L et al in a study on 57 patients in 2007 found an improvement of vertigo in 81% of patients (Class A, 61.4%; class B, 19.3%) and hearing loss (> 10 dB = SNHL) in 15.8% of patients. In their study ITG therapy was administered using a low dose of gentamicin (Approximately 21-24 mg per injection) applied at intervals of a minimum of 27 days.…”
Section: Discussionmentioning
confidence: 93%
“…[14] In a study conducted by Delgardo LP et al in 2011 on 71 patients showed an improvement of vertigo in 84.37% of patients and hearing loss in 18.3% patients. [15] De Beer L et al in a study on 57 patients in 2007 found an improvement of vertigo in 81% of patients (Class A, 61.4%; class B, 19.3%) and hearing loss (> 10 dB = SNHL) in 15.8% of patients. In their study ITG therapy was administered using a low dose of gentamicin (Approximately 21-24 mg per injection) applied at intervals of a minimum of 27 days.…”
Section: Discussionmentioning
confidence: 93%
“…We have tried to match most of the clinical and therapeutic variables but this could not be done for other parameters [2]. Thus, although we did not determine the permeability of the round window to gentamicin, we can consider that this was similar for both groups because the treatment was equally successful.…”
Section: Discussionmentioning
confidence: 99%
“…Between June 1998 and September 2007, 71 MD patients were treated with intratympanic gentamicin [2]. All the patients signed an informed consent that included the requirements established by the International Conference on Harmonization.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations